2014
DOI: 10.3389/fchem.2014.00077
|View full text |Cite|
|
Sign up to set email alerts
|

Relationships between chemical structures and functions of triterpene glycosides isolated from sea cucumbers

Abstract: Many marine triterpene glycosides have in vitro and in vivo activities with very low toxicity, suggesting that they are suitable agents for the prevention and treatment of different diseases, particularly cancer. However, the molecular mechanisms of action of natural marine compounds in cancer, immune, and other various cells are not fully known. This review focuses on the structural characteristics of marine triterpene glycosides and how these affect their biological activities and molecular mechanisms. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 117 publications
(168 reference statements)
0
39
0
Order By: Relevance
“…Triterpene glycosides bearing a 9(11)-double bond, the presence of an 18(20)-lactone in the aglycone, with at least one oxygen group adjacent to this functional moiety is substantial for their biological activity [126,132]. …”
Section: Cytotoxicity and Anticancer Activity Of Saponinsmentioning
confidence: 99%
“…Triterpene glycosides bearing a 9(11)-double bond, the presence of an 18(20)-lactone in the aglycone, with at least one oxygen group adjacent to this functional moiety is substantial for their biological activity [126,132]. …”
Section: Cytotoxicity and Anticancer Activity Of Saponinsmentioning
confidence: 99%
“…9 and 12). However, the mechanisms of induction of apoptosis and the molecular mechanism of action of the drug in cancer cells remain still elusive …”
mentioning
confidence: 99%
“…However, the mechanisms of induction of apoptosis and the molecular mechanism of action of the drug in cancer cells remain still elusive. 12 In the present study, we examined the efficacy and toxicity of FrA in human CRPC prostate cancer cells, including drug-resistant lines. We explored antitumor efficacy and toxicity in vitro and in vivo and investigated the mechanisms of action of this promising drug.…”
mentioning
confidence: 99%
“…Other researchers observed that marine triterpene glucosides such as frondoside A, cucumarioside A 2 -2, A 4 -2, and so on, had anticancer activity through different mechanisms, including increased expression of p21, p53, decreased expression of Bcl-2 and Mcl-1, increased expression of Bax, and inhibition of the noncovalent binding of topoisomerase 2α to DNA. Our group previously summarized their actions and their mechanisms [68]. Taken together, these suggest that marine triterpene glycosides may contribute to candidate anticancer agents.…”
Section: Action Mechanisms Of Stichoposides Related To Ceramide Gementioning
confidence: 97%